Improvement of Colloidal Stability in Colloidal Processing for Highly Translucent, Nanosized Zirconia - Chuin Hao Chin; Andanastuti Muchtar; Che Husna Azhari; Masfueh Razali; Mohamed Aboras (Penerbit Universiti Kebangsaan Malaysia, 2024)
Volume 47 Number 7